Necessary intentionality a study in the metaphysics of aboutness - Simchen, Ori. (Oxford : Oxford University Press, 2012)
Is it possible for the name of a particular person not to refer to that person? Ori Simchen defends a negative answer to this question and presents a new account of aboutness, or intentionality.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Intentionality (Philosophy); Metaphysics